Assessing climate change impacts on cereal production: The role of fertilizer use and GMM-based estimation - Anam, Sayedul; Rahman, Md. Azizur; Hassan, Md. Arif; Hossan, Md. Alamgir; Kobra, Mst Khadijatul (Asian Journal of Agriculture and Rural Development, 2025)
Environmental hazards cause a decline in food production, leading to food crises and overall instability among different nations. This scenario is more prevalent in the case of cereal production in some developing countries, particularly in South Asian regions. In line with this, research has been conducted to examine the impacts of climate change variables (rainfall, temperature, carbon dioxide emissions, methane emissions, nitrous oxide emissions) and control variables such as cereal production and fertilizer use on cereal output. The analysis considers cereal productivity while incorporating secondary data. A two-step Generalized Method of Moments (GMM) approach has been applied, considering eighteen top productive countries as dependent variables, with climate variables and control variables to analyze their connectivity. The study found that climate change variables significantly affect cereal production across the sample countries, except for methane emissions. Additionally, fertilizer use contributes to increased cereal crop yields. The findings are valuable for policymakers to identify specific negative effects of climate variables and adopt effective strategies to enhance cereal production. Ultimately, updating policies, applying modern farming techniques, and employing skilled human resources should be prioritized to address these challenges.